Sub-Disciplines in Security Sciences: On the Need to Distinguish Them - Janusz Gierszewski (Polish Political Science Yearbook, 2023)
The article attempts to address the issue of the need to distinguish sub-disciplines in security sciences. A scientific discipline is a basic and lowest-order category within the classification system of individual fields of science. Security science in Poland has been classified as one of many disciplines in the field of social sciences. The problem was formulated as a question: based on which criteria can sub-disciplines be distinguished in the security sciences? The aim is to identify the basic sub-disciplines in security sciences and to propose a criterion for their distinction. Critical literature analysis and research design were adopted as the primary methods. There is no established criterion for the division into individual sub-disciplines in Poland. The author proposes to distinguish sub-disciplines based on the following criteria: theoretical, practical, types of institutions, and levels of organization of different security sectors. It is based on the assumption that security sciences require a clarification of the substantive scope within sub-disciplines through which the discipline’s identity can be built up, and research can be carried out as part of further scientific work.